Conductivity and mechanical properties of PEO/PVA/UiO-66 composite polymers for membrane of lithium-ion batteries - Patah, Aep; Rochliadi, Achmad; Husein, Aditya; Ramadhan, Dadang (Communications in Science and Technology, 2024)
Lithium batteries are crucial for energy storage in electronics, transportation, and industrial sectors. However, lithium-ion battery separators such as Celgard require significant improvements, particularly in ionic conductivity (?). Combining Metal-Organic Frameworks (MOFs) with polymers is expected to create a separator membrane that enhances conductivity and mechanical properties in lithium-ion batteries. UiO-66 MOFs were synthesized using the solvothermal method at 120? and then composited with polyethylene oxide (PEO) and polyvinyl alcohol (PVA) polymer membranes using the solution casting method. The UiO-66 MOFs/PEO/PVA polymer composites were made by varying the UiO-66 content from 2% to 8% (w/w) while keeping a constant LiPF6 concentration of 9% (w/w). These composites were characterized using X-ray Diffraction (XRD) and Fourier-Transform Infrared spectroscopy (FTIR). Subsequently, the EIS test and tensile tests assessed the performance of the composite membranes. The resulting membrane with 6% (w/w) UiO-66 MOFs exhibited a conductivity (?) of 5.60 × 10–3 S cm–1 and a tensile strength of 32.5 MPa.